Clinical Presentation and Outcomes of Covid-19 in Maintenance Hemodialysis Patients in Pakistan: A single-Center Study - Yaqub, Soniya; Hamid, Amna; Naeem, Zarghoona; Awan, Safia (Pakistan Journal of Kidney Diseases, 2021)
The objective of the present study was to review clinical presentation and short-term outcomes of COVID-19 in patients on maintenance hemodialysis (MHD). The study was conducted at three coordinated outpatient hemodialysis units at Aga Khan University Hospital from 1st May 2020 to 31st July, 2020. METHODOLOGY: Detailed analysis of 15 patients on MHD diagnosed with COVID-19 during the study period was done along with comparison between surviving and deceased subjects. RESULTS: Out of 108 MHD patients, 17 were diagnosed with COVID-19 through polymerase chain reaction (PCR) and 15 of them were included in the study. Mean age of subjects was 62.8 years; 53.3% were females. Median HD vintage was 15 months (IQR 8-14). Forty percent of the patients were asymptomatic. Frequent symptoms observed were shortness of breath (40%), cough (26.7%) and fever (20%). Lymphopenia was not seen in our study and 40% had no radiographic finding. Acute respiratory distress syndrome, myocardial injury, hepatic dysfunction and thrombotic event were observed complications. Compared to survivors, deceased patients were significantly older (p=0.01) and had higher inflammatory markers including C-reactive protein, ferritin, procalcitonin, lactate dehydrogenase. Forty percent were hospitalized and 83.3% required ventilation (invasive or noninvasive). By the end of follow up; 40% patients died. CONCLUSION: Patients on MHD are susceptible to severe COVID-19 and higher mortality. Asymptomatic presentation demands high clinical suspicion for prompt diagnosis. Following trend of inflammatory markers may help clinician in identification of severe cases and appropriate management.